Two-Tier System of Judgments and Orders (Nature of the Separate Order to Pay or Fulfil the Claim) - Kirkutis Mykolas; Jokubauskas, Remigijus; Bolzanas Darius; Visinskis, Vigintas (LeXonomica, 2021)
The quality of procedural judicial documents is one of the most important components of judicial proceedings. The trust of individuals and the public in the judicial system may also depend on the quality of these documents. Therefore, Lithuanian legislation sets certain standards for procedural judicial documents. As well as, the law also provides for certain possibilities to eliminate ambiguities in court procedural documents both after the court decision has been made and during enforcement proceedings. Povzetek. Kakovost sodnih procesnih aktov je eden najpomembnejših elementov sodnih postopkov. Od kakovosti teh aktov je lahko odvisno tudi zaupanje posameznikov in javnosti v pravosodni sistem. Zato litovska zakonodaja določa določene standarde za procesne sodne akte. Poleg tega zakon določa tudi nekatere možnosti za odpravo nejasnosti v sodnih procesnih aktih tako po izdaji sodne odločbe kot med postopkom izvršbe.